Lecture Room Design Towards the New Normal Pandemic Covid 19 (Lecture Room Case Study at UPN “Veteran” Jawa Timur) - Djuni, Erwin; Agustin, Dyan (Future Science, 2020)
Classroom design management is very important for the continuity of the learning process, especially in a university. At the time of the current Covid 19 pandemic, the learning process has now turned online without using classrooms. But this certainly cannot go on continuously. The government has launched the New Normal program, which means that all activities are slowly being carried out again but with a maximum health protocol including the lecture learning process. The condition of the Covid 19 pandemic requires a lecture room design that can adapt to the needs of health protocols to break the chain of the spread of the virus. The purpose of this study is to analyze the types of activity in the lecture hall and the facilities needed so that a lecture room design can be obtained by the current conditions of the Covid 19 pandemic. The method used is qualitative deductive by describing the conditions of the lecture room and distributing questionnaires to students by filling out online questionnaires. The results of the study, in terms of seat arrangement according to the new normal, show that the type that can accommodate students the most is the rectangle type with an average capacity of 40% of normal capacity. Meanwhile, the design of the barrier between students is needed in the lecture hall to avoid droplets and to make it safer and more comfortable to attend lectures. In the existing door handle, an additional handle is designed so that it can open the door not by hand but my arm. Thus, it is hoped that the design of the new normal lecture room can break the chain of spreading covid 19.